Golden State - Winters, Ben H (Mulholland Books, Little, Brown and Company, 2019)
A veteran of the Speculative Service in an alternate-world California where the law and truth are valued above all else uses his rare authority to question the facts when truth enforcement is manipulated for corrupt purposes.